DYNAMICS OF VIEWS ON ETHICS OF PEDAGOGICAL DIAGNOSTICS IN INFORMATION AND COMMUNICATION LEARNING ENVIRONMENT - Oleksandr Kolgatin (Kherson State University, 2016)
Didactical demands for pedagogical diagnostics and its realisation specific characters in information and communication learning environment of university are analysed. The questions of ethics and information security of pedagogical diagnostics are considered. Ethic aspects, connected with using of the automated pedagogical diagnostic systems, are underlined. Results of survey of students about their view points on issues of security of pedagogical diagnostics data are discussed.